Improving Performance of Zakat Institution in Poverty Alleviation: Balanced Scorecard Approach - Sulastiningsih Sulastiningsih; Suci Utami Wikaningtyas; Dwi Novitasari (Tazkia Islamic Finance and Business Review, 2020)
The purpose of this study is to develop a performance improvement model of Zakat Institution in Indonesia (OPZIS) using four balanced scorecard perspectives in poverty alleviation. The model is examined by using Structural Equation Modeling (SEM) analysis. Respondents of this study was 100 employees of 11 Zakat Institution, 100 muzzaki and 100 mustahiq. The results of this study prove that the Balanced Scorecard approach as a strategic management model can improve Zakat Institution performance. The quality of Zakat Institution performance is influenced by the organization's ability to grow and become a learning organization with training and support from supervisors. Good internal processes are created by employee satisfaction and loyalty, which ultimately affects the quality of customer service. Good quality customer service will affect customer satisfaction, which in turn, customers become  more loyal and affect Zakat Institution financial performance. High financial performance will increase the contribution of Zakat Institution in poverty alleviation. This is because Zakat Institution is able to properly channel the funds to those entitled to receive it, namely the poor.